OBTAINING NEW ANTICORROSION COATINGS BASED ON ETHANOLAMINES - Beknazarov Hasan Soyibnazarovich; Ishonqulova Gulhon Tagaymurotovna; Ishanqulova Mehri Muratovna (European Science Publishing, 2025)
This study focuses on the development of new anticorrosion coatings based on ethanolamines. Chemical modification of monoethanolamine (MEA), diethanolamine (DEA), and triethanolamine (TEA) was performed to enhance their interaction with polymer matrices and metal surfaces. The resulting coatings exhibited excellent adhesion, improved barrier properties, and high resistance to corrosion in aggressive environments such as saline, acidic, and alkaline solutions. Electrochemical tests and salt spray experiments confirmed the effectiveness of ethanolamine-based coatings in preventing both uniform and localized corrosion. These findings demonstrate that ethanolamines are promising materials for the creation of environmentally friendly and efficient anticorrosion coatings for industrial applications.
Keywords: Ethanolamines, Anticorrosion coatings, Metal protection, Polymer matrices, Corrosion resistance, Chemical modification, Salt spray test, Electrochemical impedance.